Guidance and Control System Design of a Surface-to-Air Missile Based on 122 mm Rocket - Yogaswara, Y. H.; Alvin Ardiansyah; Rianto Adhy Sasongko; Taufiq Mulyanto (Indonesian Journal of Aerospace, 2025)
This paper applies and analyzes the design of a proportional navigation guidanceand control system for a 122 mm rocket platform. The research involves modeling missiledynamics, guidance systems, and control systems. The missile dynamics model relies onthe 6 DOF (Degrees of Freedom) equation for a rigid body, with aerodynamic data obtainedfrom the Missile Datcom program. The propulsion model is generated by a genericthrust profile of a 122 mm unguided rocket. The guidance system model is based on theproportional navigation guidance law, and the control system model employs the LinearQuadratic Regulator (LQR) method. Modeling is conducted using Simulink software, andsimulations encompass various scenarios. The analysis considers aspects such as missiletrajectory, acceleration command, actual acceleration, control surface deflection, and thetime required to hit the target. The simulation results indicate the missile’s capability tointercept targets under numerous conditions, although limitations are observed in specifictarget scenarios where interception is not achievable.